2021
DOI: 10.1021/acsaem.1c00453
|View full text |Cite
|
Sign up to set email alerts
|

Facile Molten Vanadate-Assisted Surface Treatment Strategy for Li2MnO3 Activation of Li-Rich Cathode Materials

Abstract: Li-rich transition metal oxides (Li 1+X M 1−X O 2 ) are known as the next generation of cathode materials for lithium-ion batteries by reason of their high specific capacity. However, oxygen release and structural conversion in Li-rich layered oxides during the initial charge result in low initial Coulomb efficiency (ICE) and uninterrupted capacity attenuation. In this paper, we show a molten vanadate-assisted strategy at low temperature combined with washing treatment to regulate the amount of labile oxygen r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…The XPS spectra of Ni, Mn, Na, and K are also shown in Figure d–h. The Mn 2p band at 642.2 eV with a + 4 valence state was almost not influenced by the doping of Na and K whereas the presence of the peaks at 1072 and above 290 eV evidences the successful doping of Na and K, respectively, as shown in Figures S6 and S7. The Ni 2p 3/2 peaks could be deconvoluted into two components of Ni 2+ and Ni 3+ and the O 1s peaks into three components of surface oxygen vacancies (SOVs), lattice oxygen (LO), and surface adsorbed oxide species (SO) from which their corresponding percentages could be estimated, , as shown in Figure f.…”
Section: Resultsmentioning
confidence: 89%
“…The XPS spectra of Ni, Mn, Na, and K are also shown in Figure d–h. The Mn 2p band at 642.2 eV with a + 4 valence state was almost not influenced by the doping of Na and K whereas the presence of the peaks at 1072 and above 290 eV evidences the successful doping of Na and K, respectively, as shown in Figures S6 and S7. The Ni 2p 3/2 peaks could be deconvoluted into two components of Ni 2+ and Ni 3+ and the O 1s peaks into three components of surface oxygen vacancies (SOVs), lattice oxygen (LO), and surface adsorbed oxide species (SO) from which their corresponding percentages could be estimated, , as shown in Figure f.…”
Section: Resultsmentioning
confidence: 89%
“…If d E is linear with d √τ, then this applies to the equation In eq , τ is the relaxation time, 600 s; n is the amount of substance of active material; V m is the molar volume; Δ E s is the variation of voltage by impulse; and Δ E t is the variation of voltage in constant-current charging (or discharging). Figure a–d shows a linear relationship between d E and d √τ, so all four samples apply to eq …”
Section: Resultsmentioning
confidence: 99%
“…In eq 3, τ is the relaxation time, 600 s; n is the amount of substance of active material; V m is the molar volume; ΔE s is the variation of voltage by impulse; and ΔE t is the variation of voltage in constant-current charging (or discharging). Figure 9a−d shows a linear relationship between dE and d√τ, so all four samples apply to eq 33 33 The distribution of the diffusion coefficient of Li + describes the activity of Li + in the process of charge and discharge. First of all, the increase of cobalt content makes D Li + GITT increase significantly.…”
Section: Resultsmentioning
confidence: 99%
“…Our research group adopted a simple vanadate heat treatment method to construct a lithium concentration gradient material which vastly enhanced the initial Coulombic efficiency and distinctly suppressed voltage attenuation. 22 In this work, we applied (NH 4 ) 2 SiF 6 to react with LLOs at 700 °C to form LiF and Li 2 SiO 3 on the surface of LLOs (Figure 1). As a result, the removing of Li 2 O from LLOs leads to the formation of Li and O vacancy on the surface of the material.…”
Section: Introductionmentioning
confidence: 99%
“…They demonstrated that the construction of a Li-poor phase can help remove the Li–O–Li bond on the surface and even replace Li–O–Li with Li–TM–Li, which immensely reduce the irreversible redox of anions and distinctly improved the initial Coulombic efficiency and cycling performance of LLOs. Our research group adopted a simple vanadate heat treatment method to construct a lithium concentration gradient material which vastly enhanced the initial Coulombic efficiency and distinctly suppressed voltage attenuation . In this work, we applied (NH 4 ) 2 SiF 6 to react with LLOs at 700 °C to form LiF and Li 2 SiO 3 on the surface of LLOs (Figure ).…”
Section: Introductionmentioning
confidence: 99%